Expression of clusterin, XIAP and survivin, and their changes by camptothecin (CPT) treatment in CPT resistant PC-3 and CPT-sensitive LNCaP cells - Mizutani, K.; Matsumoto, K.; Hasegawa, N.; Deguchi, T.; Nozawa, Y. (Experimental Oncology, 2006)
Aim: Clusterin and IAPs (inhibitor of apoptosis proteins), such as survivin and XIAP, are known to be related to chemo-resistance in several cancer cells. In the current study, we investigated their expression levels in human prostate cancer cell lines, LNCaP and PC-3 which are sensitive and resistant to camptothecin (CPT), topoisomerase I inhibitor, respectively. Methods: LNCaP and PC-3 cells were cultured in the presence of CPT, cell death was evaluated using Hoechst 33342 and propidium iodide (PI) double staining. The expression of clusterin, XIAP and survivin on mRNA and protein levels was investigated by semi-quantitative RT-PCR and Western blotting, respectively. Results: Our data showed that 24 h treatment of LNCaP cells with 0.5 and 3.0 µM CPT resulted in higher number of apoptotic cells, than that in PC-3 cells. Western blot analysis revealed that the clusterin level in PC-3 cells was 5-fold higher than that in LNCaP cells. In contrast, XIAP expression level in PC-3 cells was lower than that in LNCaP cells, and survivin levels were similar in these two cell lines. Treatment with 0.5 and 3.0 µM CPT resulted in the reduced survivin and XIAP expression in both cell lines, while clusterin expression remained unchanged in LNCaP cells, but was increased in PC-3 cells. Conclusion: The results suggest that clusterin may take a greater part in CPT-resistance than survivin and XIAP in PC-3 cells.